Cross-Cultural Comparison of Personality Traits, Attachment Security, and Satisfaction With Relationships as Predictors of Subjective Well-Being in India, Sweden, and the United States. (September 2016) - Galinha, Iolanda Costa; Garcia-Martin, Miguel Ángel; Oishi, Shigehiro; Wirtz, Derrick; Esteves, Francisco
Personality traits like Neuroticism and Extroversion, Satisfaction With Relationships, and Attachment Security are among the most important predictors of subjective well-being (SWB). However, the relative contribution of these predictors to SWB is seldom tested, and even more rarely tested cross-culturally. In this study, we replicate and extend Galinha, Oishi, Pereira, Wirtz, and Esteves, aiming to identify the strongest predictors of SWB, and in what way that contribution is universal or culture-specific, across such collectivist-individualist countries as India, Sweden, and the United States ( N = 1, 622). Structural equation modeling showed that Satisfaction With Relationships is a stronger predictor of SWB in India, while Neuroticism is a stronger predictor of SWB in Sweden and the United States, results consistent with prior Portuguese and Mozambican samples. These findings suggest that Satisfaction With Relationships is probably a stronger predictor of SWB in more collectivistic and less developed countries, while low Neuroticism is a stronger predictor of SWB in more individualistic and highly developed countries. Across all samples, Attachment Security and Extroversion showed very weak or nonsignificant effects on SWB above the contribution of Neuroticism and Satisfaction With Relationships, consistent with prior results. Neuroticism significantly mediated the relationship between Attachment Security, SWB, and Satisfaction With Relationships.